TRADITIONAL ELEMENTS AND TRANSFORMATION IN PERFORMANCE: A STUDY OF THE GUZHENG CONCERTO NIGHT MOORING AT MAPLE BRIDGE - Guo , Qianru; Tee , Xiao Xi (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2026)
Night Mooring at Maple Bridge is a guzheng concerto that fuses traditional Chinese elements into a modern composition. The work, based on classical poetry, folk idioms and operatic traditions, reshapes traditional resources in modern Chinese instrumental music. This study examines the work in two complementary sections: structural and compositional analysis on the basis of the piano reduction score and performance interpretation. The compositional dimension is analysed using score-based study of elements borrowed from Kunqu opera, Jiangnan sizhu, southern Jiangsu folk song styles, and classical poetic imagery and how these affect melodic, tonal and structural design. These elements are transformed rather than directly quoted, forming a modern musical idiom. The performance aspect investigates the achievement of these transformed elements. Through score analysis and performance-based listening, articulation, tempo, and techniques such as glissando, scraping, and tremolo reveal how interpretation shapes poetic atmosphere and expression. The results indicate that traditional components in Night Mooring at Maple Bridge do not only perform at the compositional design level but also reconfigure further by embodied performance. The connection between structural analysis and performance interpretation makes the proposed study add to the body of performance-informed studies on modern guzheng repertoire and provides insights that others can apply to Chinese instrumental performance and pedagogy.